A new model for predicting fluid loss in fracture-porosity reservoir - Liu, Jinjiang; Zhang, Fuxing; Qian, Peng; Wu, Wenlin (Oil & gas science and technology, 2021)
Drilling fluid loss always occurs in fracture-porosity reservoirs and it causes severe problems. To reduce and prevent lost circulation, it is important to get to know the cause and the characteristic of drilling fluid loss. According to the approach in the reservoir simulation and well test analysis, a new model for drilling fluid loss in fracture-porosity reservoir is presented. Multi fractures in the formation and drilling fluid seepage between fracture and rock matrix have been considered in the model. The governing equations are derived based on the principle of conservation of mass. The model is solved numerically using Newton-Raphson iterative method. The obtained results indicate that drilling fluid leak-off has great influence on the total leakage volume. It is necessary to consider the impact of the drilling fluid leak-off. In addition, influence of formation properties, such as fracture stiffness, rock matrix porosity, rock matrix permeability, and operation factors, such as pressure difference between wellbore and formation, are also analysed in detail in the paper which could help better understand the factors that influence the drilling fluid loss during drilling operation.